Development of a novel prevention bundle for pediatric healthcare-associated viral infections. (20th July 2018) - Hei, Hillary; Bezpalko, Orysia; Smathers, Sarah A.; Coffin, Susan E.; Sammons, Julia S.
Abstract: Objective: To reduce the healthcare-associated viral infection (HAVI) rate to 0.70 infections or fewer per 1, 000 patient days by developing and sustaining a comprehensive prevention bundle. Setting: A 546-bed quaternary-care children's hospital situated in a large urban area. Patients: Inpatients with a confirmed HAVI were included. These HAVIs were identified through routine surveillance by infection preventionists and were confirmed using National Healthcare Safety Network definitions for upper respiratory infections (URIs), pneumonia, and gastroenteritis. Methods: Quality improvement (QI) methods and statistical process control (SPC) analyses were used in a retrospective observational analysis of HAVI data from July 2012 through June 2016. Results: In total, 436 HAVIs were identified during the QI initiative: 63% were URIs, 34% were gastrointestinal infections, and 2.5% were viral pneumonias. The most frequent pathogens were rhinovirus (n=171) and norovirus (n=83). Our SPC analysis of HAVI rate revealed a statistically significant reduction in March 2014 from a monthly average of 0.81 to 0.60 infections per 1, 000 patient days. Among HAVIs with event reviews completed, 15% observed contact with a sick primary caregiver and 15% reported contact with a sick visitor. Patient outcomes identified included care escalation (37%), transfer to ICU (11%), and delayed discharge (19%). Conclusions: The iterative development, implementation, and refinement of targeted prevention practices was associated with a significant reduction in pediatric HAVI. These practices were ultimately formalized into a comprehensive prevention bundle and provide an important framework for both patient and systems-level interventions that can be applied year-round and across inpatient areas.